LEARNING MEDIA VARIATION: STUDENTS’ PERCEPTION - I Gde Putu Agus Pramerta; Ida Bagus Ari Arjaya; Putu Ayu Trisna Devi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2022)
Covid-19 has changed the ways of the teaching-learning process. Classroom activities are done with the use of technology and its varied platforms. This research aimed at describing the learning media variation for the learning process by considering the students’ perceptions. The participant is one class of eight grade students of SMP (SLUB) Saraswati 1 Denpasar. This research is a descriptive study. The data was collected by filling out an online questionnaire with Google forms and interviews. The result showed the indication of having variation in the learning media and, interestingly, the use of Google Classroom is considered effective for the students, but the teaching-learning process is done in face-to-face learning. It implies that learning variation is needed to support and facilitate classroom practice. Further study needs to be conducted for the sake of having in-depth studies related to learning variation in a face-to-face or hybrid context with a bigger number of participants.